THE EFFECT OF INTERACTIVITY AND SHOPEE LIVE PROMOTIONS ON IMPULSE BUYING OF NAJMIA BEAUTY CONSUMERS IN SEMARANG CITY - Feby Sekonda Lestyowati; Nurchayati Nurchayati; Gita Sugiarti; Heru Eko Prasetyo (Universitas Nusa Cendana, 2026)
The influence of interactive elements and promotional initiatives within the Shopee Live platform on spontaneous purchase tendencies among patrons of Najmia Beauty in Semarang Municipality was investigated through this inquiry. A quantitative methodology was adopted, whereby empirical evidence was gathered via digital surveys disseminated to individuals who had engaged with and transacted through Najmia Beauty's live broadcasts. Purposive selection was applied to recruit 100 participants. Statistical evaluation of the dataset was conducted employing multivariate linear modeling, facilitated by SPSS software version 25. Positive and statistically meaningful associations were revealed between interactive dynamics and promotional efforts, on one hand, and patrons' unplanned acquisition patterns, on the other. Bidirectional engagement in real-time broadcasts, coupled with fleeting incentive schemes, was found to foster abrupt buying choices. Such outcomes suggest that refined dialogic exchanges and incentive frameworks in livestream merchandising can robustly provoke impromptu consumer actions. Nonetheless, constraints arise from the inquiry's confinement to a singular brand and locale. Subsequent investigations are thus advised to incorporate supplementary factors while broadening contextual and territorial dimensions for more holistic insights. Keywords: Interactivity; Promotion; Impulse Buying